A cross-sectional analysis of antibiotic use: Attitudes and practices in the Albanian community - Silvi Bozo; Elena Capparelli; Eftiola Pojani (Elsevier, 2024)
Background: Antibiotic resistance (AR) represents a global health challenge. Within the coordinated efforts to tackle AR, community education is a key strategy to enhance awareness and improve antibiotic use. The current study intends to investigate the Albanian community's attitude and practices regarding antibiotic use, including recent health related developments, like COVID-19. Methods: A cross sectional survey was conducted among Albanian residents between December 2022 and March 2023, using a standardized questionnaire which featured three sections covering demographic data, attitudes, and practices regarding antibiotic use. Statistical analysis included both descriptive statistics and the Chi-square test to assess relationships between categorical variables. Results: The questionnaire was effectively completed by 519 participants. The majority were females (70.1 %) within the 18-30 age range (55.5 %) and had a college/university degree (93.3 %). 53.4 % reported antibiotic use without a medical prescription, with amoxicillin and azithromycin being the most used antibiotics. Commonly cited reasons for antibiotic use were self-reported symptoms such as flu/common cold, sore throat, cough, and fever (82.3 %). 69.0 % reported following prescribed antibiotic courses, with higher adherence among females and those with higher education. Awareness of AR was considerable (78.0 %), with females evidencing more awareness compared to males. Only 34.3 % of participants reported antibiotic use for COVID-19, mostly after testing positive, with azithromycin being the most frequently used antibiotic. Conclusions: Our study highlights concerning trends in antibiotic self-medication and awareness gaps in prudent antibiotic use emphasizing the need for tailored educational programs, regulatory oversight, and robust surveillance systems in Albania's healthcare.